Performance Effects of Different Shutdown Methods on Three Electrode Materials for Electromethanogenesis - Nils Rohbohm; Maren Lang; Johannes Erben; Kurt Gemeinhardt; Nitant Patel; Ivan K. Ilic; Doris Hafenbradl; Jose Rodrigo Quejigo; Largus T. Angenent (ChemElectroChem)
Abstract Industrial applications of microbial electrochemical systems will require regular maintenance shutdowns, involving inspections and component replacements to extend the lifespan of the system. Here, we examined the impact of such shutdowns on the performance of three electrode materials (i. e., platinized titanium, graphite, and nickel) as cathodes in a microbial electrochemical system that would be used for electromethanogenesis in power‐to‐gas applications. We focused on methane (CH4) production from hydrogen (H2) and carbon dioxide (CO2) using Methanothermobacter thermautotrophicus. We showed that the platinized titanium cathode resulted in high volumetric CH4 production rates and Coulombic efficiencies. Using a graphite cathode would be more cost‐effective than using the platinized titanium cathode in microbial electrochemical systems, but showed an inferior performance. The microbial electrochemical system with the nickel cathode showed improvements compared to the graphite cathode. Additionally, this system with a nickel cathode demonstrated the fastest recovery during a shutdown experiment compared to the other two cathodes. Fluctuations in pH and nickel concentrations in the catholyte during power interruptions affected CH4 production recovery in the system with the nickel cathode. This research enhances understanding of the integration of biological and electrochemical processes in microbial electrochemical systems, providing insights into electrode selection and operating strategies for effective and sustainable CH4 production.